Stroke 2021
DOI: 10.36255/exonpublications.stroke.timingischemicstroke.2021
|View full text |Cite
|
Sign up to set email alerts
|

Timing the Ischemic Stroke by Multiparametric Quantitative Magnetic Resonance Imaging

Abstract: The advent of recanalization therapies has transformed the management of acute ischemic stroke patients. The timing of symptom onset is one of the key criteria for selecting the recanalization method as pharmacological and nonpharmacological recanalization therapies are only safe when administered within strict, but evolving, time windows. Magnetic resonance imaging (MRI) reveals ischemia within minutes and estimates ischemia duration in brain parenchyma. Preclinical studies have shown that by combining diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Abi sekos lyginamos kartu -ADC ir difuzijos restrikcijos sekų radiniai geriausiai išryškėja praėjus 2-4 valandoms po insulto. Vertinant FLAIR seką hiperūmiu (hyperacute) laikotarpiu, jokių specifinių radinių nebūna, tuo tarpu difuzijos restrikcijos sekoje randami pokyčiai, kurie gali padėti nustatyti, kad insultas įvyko mažiau nei prieš 4,5 valandos, kai nėra žinoma insulto pradžia [13]. Kai kuriais atvejais FLAIR sekoje praėjus 3-6 valandoms gali būti randama parenchimos pokyčių, todėl gali būti sudėtinga parinkti tinkamą gydymo taktiką [14].…”
Section: Išeminio Insulto Diagnostika Magnetinio Rezonanso Tyrimuunclassified
“…Abi sekos lyginamos kartu -ADC ir difuzijos restrikcijos sekų radiniai geriausiai išryškėja praėjus 2-4 valandoms po insulto. Vertinant FLAIR seką hiperūmiu (hyperacute) laikotarpiu, jokių specifinių radinių nebūna, tuo tarpu difuzijos restrikcijos sekoje randami pokyčiai, kurie gali padėti nustatyti, kad insultas įvyko mažiau nei prieš 4,5 valandos, kai nėra žinoma insulto pradžia [13]. Kai kuriais atvejais FLAIR sekoje praėjus 3-6 valandoms gali būti randama parenchimos pokyčių, todėl gali būti sudėtinga parinkti tinkamą gydymo taktiką [14].…”
Section: Išeminio Insulto Diagnostika Magnetinio Rezonanso Tyrimuunclassified
“…MRI-based techniques have been adopted to stratify stroke patients with an unknown time of onset. However, image evaluation generally relies on clinical experience, which is inevitably subjective [11]. Existing evidence has shown that the performance of imaging in estimating stroke onset time needs to be improved [12].…”
Section: Introductionmentioning
confidence: 99%